Multiple Mini Interview (MMI) student selection 2023/2024 - Mahfudz, Anis Shafina (Faculty of Medicine, 2023)
Determining the future generation of medical doctors is a daunting task burdened with significant responsibilities and enormous consequences. Since 2019, the Faculty of Medicine UiTM has been conducting Multiple Interviews (MMI) to recruit medical students into their UiTM Bachelor of Medicine & Bachelor of Surgery (MBBS) program. For the 2023/2024 MBBS student intake, the MMI selection session was jointly organized by the Academic Office & Department of Medical Education (DoME) over a two-day period from 31th May to 1st June 2023 in UiTM Faculty of Medicine, Selayang Campus.